Analisis Pengaruh Kemampuan Keuangan Daerah dan Kemandirian Keuangan Daerah Terhadap PDRB Perkapita Kota Banjarmasin - Hamiddah Lianita; Yunita Sopiana (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the ratio of regional financial capacity and the ratio of regional financial independence and their influence on GRDP per capita in Banjarmasin City. The data used in this study is secondary data consisting of data from the APBD and GDRP per capita of Banjarmasin City in 2010-2019. The analytical technique used is quantitative analysis by measuring the ratio and multiple linear regression. Analyzed using Eviews version 10 program.The results obtained from this study indicate that the regional financial capacity in Banjarmasin City in 2010-2019 is in the